Reconstruction of Sanctions Regulations against Notaries Who Do Not Read Deed before Patient as an Effort to Protect Patient by Law - Angelia, Ister; Suhartono, Slamet; Prasetyawati, Endang; Mangesti, Yovita Arie (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Notary is a public official needed by the community who needs a deed as evidence for civil transactions. A notarial deed is perfect evidence that does not require other evidence in court proceedings. The authenticity of the Notarial Deed is required to be made by an Official whose authority is granted by law. In addition, one of the requirements for the authenticity of a Notarial deed must be read out in front of the person appearing before it is signed. If the Notary does not read out the deed, the result is that its evidentiary power is degraded to a deed under hand, while the Notary is not subject to any sanctions. Such regulation is unfair to the person appearing, so for justice for the person appearing, the regulation of sanctions in the UUJN must be reconstructed by deleting and changing several provisions of the articles containing sanctions. This research is normative legal research that focuses on the study of legal norms of UUJN, especially those related to the obligation of Notaries to read the deed in front of the person appearing before the deed is signed. The reconstruction is carried out by adding one letter m in the articles containing sanctions for Notaries who do not carry out their obligations, including not carrying out the obligation to read the deed before the deed is signed.